A Systematic Review of Trend STEM Education Research on Physics Learning in Indonesia - Yulianti, Dwi; Faiz Fajar Shafira; Putut Marwoto; Siti Noviyatun (Universitas Negeri Semarang, 2025)
STEM education can contribute to the achievement of students' thinking skills, such as 21st-century learning skills (critical thinking, creative thinking, collaboration, communication), literacy, and numeracy, which are crucial to develop in every school learning activity, especially in physics learning. These skills are essential for students to prepare a resilient generation to face global challenges related to rapid technological advances, the Industrial Revolution 4.0, socio-cultural shifts, environmental changes, and future world differences. This research study aimed to systematically analyze trends of STEM Education research on physics learning in Indonesia based on articles published in national journals (SINTA). Fifty-four articles were collected from Physics Education journals in Indonesia between 2019 and 2024, with STEM Physics learning as the main point of this research. The current study revealed that STEM Physics research publications had improved annually for the past 5 years. The types and designs mostly used are Research and Development (RnD). Senior High School is the most researched subject. The physics topics mainly researched are Wave and Heat & Temperature. The most dominant treatments in STEM Physics research are Project-Based Learning (PjBL). The most dominant part of skill aspects researched is creative thinking. In addition, the most common data analysis used in STEM Physics research is N-Gain. Several recommendations have been made for future research, including increasing the diversity of research types, choosing more appropriate physics learning techniques, and aiming for relevant skills for the students. By mapping trends in research focus, methods, and skills targeted, this study helps identify gaps and opportunities for innovation in teaching practices. Teachers can use the findings to design learning models that are more diverse, relevant, and engaging, while policymakers can use the evidence to formulate educational policies that strengthen 21st-century competencies. This study's findings should be a reference for the development of innovative and inclusive educational regulations and teaching approaches for a better future generation.